An exploratory survey: experiences and perceptions of community members who have accessed pre-hospital Emergency Medical Service in Langa, Cape Town - Bam, Zina (Division of Emergency Medicine, 2020)
Background: Calling an ambulance is the first line for citizens in dealing with many healthcare emergencies. It is crucial for the caller to convey correct information regarding the patient’s emergency and on-scene location to the emergency services, resulting in prompt dispatch of correct emergency resources to the exact location. Although there is a good deal of focus on emergency medicine time parameters and outcomes, little is known about the experiences, perceptions and satisfaction level from those who have accessed pre-hospital Emergency Medical Services. Methods: A telephonic survey was conducted on individuals who had recently called for an ambulance, from the urban township of Langa, Cape Town. Surveys were conducted in the caller’s home language, using a standardized tool for collecting quantitative data around the call process, caller satisfaction, outcomes of the call, and issues experienced. Results: During June 2018, 50 callers completed the survey (69% response rate). Most callers (88%) used a personal mobile phone, and 83% called predominantly for medical problems in the daytime. Callers accessed the service by dialling a variety of emergency phone numbers. Callers were largely satisfied with the call (66%), and there were fewer language mismatches than expected. A need for better communication regarding ambulance status and over the phone medical advice was identified. A substantial number of inconsistencies were reported between callers’ outcomes and those from emergency communication centre which require further analysis. These inconsistencies, pointed into gaps within the emergency communication centre’s collecting and database system Conclusion: The study provided the first insight into pre-hospital emergency caller experiences and perceptions, highlighting important aspects perhaps not revealed through other metrics. Measurement of caller satisfaction can be a useful quality improvement tool, and would seem feasible without substantial resources. Further investigation into data capturing system and identification of call outcomes are recommended.